Konten Video Parodi pada Platform Digital dalam Perspektif Pelindungan Hak Cipta dan Doktrin Fair Use - Shafira Shava Rahmanissa; Sudjana Sudjana; Sudaryat Sudaryat (Al-Adl : Jurnal Hukum, 2023)
Parody video content on digital platforms is generally made by imitating previous works, but in it, there are also characteristics of parody makers that are different from the original work. The purpose of this study was to determine the application of the fair use doctrine, namely the doctrine that allows the use of copyrighted material without the creator's permission concerning parody video content on digital platforms and to describe the copyright protection of parody video content reviewed under Law Number 28 of 2014 concerning Copyright. This research is normative legal research by examining library materials or secondary data. The approach method used is a conceptual approach (conceptual approach), statutory approach (statute approach), and comparative approach (comparative approach). The data were obtained through a literature study using primary, secondary and tertiary legal materials. These data were processed and analyzed, then presented in a qualitative descriptive manner. The results of the study show that the application of the fair use doctrine to parody video content on digital platforms is limited in some instances. Parody video content can be considered fair use if it meets the indicators required in the provisions of Article 43 letter d or Article 44 paragraph (1) letter a UUHC. These indicators include being non-commercial, benefiting the creator or copyright holder of the original work, or he expresses no objection, or as long as the parody video content mentions and includes the full name of the creator or copyright holder of the original work, aims to criticize an issue, and does not harm the interests of the original work. From the creator or the copyright holder of the original work. Copyright protection can apply to parody video content on digital platforms made with the permission of the creator or copyright holder of the original work and are original, namely as derivative works. However, parody video content does not meet the requirements as a derivative work or is even proven to violate Copyright. In that case, it cannot be protected unless it is considered fair use.